ISLAMIC PHILOSOPHICAL TRADITION: Knowledge and Man’s Path To God - Wawan Abdullah (Universitas Islam Depok, 2023)
Islamic civilization has given birth to no less than 300 philosophers, therefore every Islamic or Arabic philosophy has a special tradition that no other tradition has. The philosophical tradition in Islam is a creative work born from the worldview of Islam. It is a system of beliefs, thoughts and values, which is projected by the word of God through tafaqquh, bayan, interpretation, takwil, and is developed in the Islamic scientific tradition. Islamic philosophy grows from revelation and then develops within scientific traditions, such as fiqh, interpretation, kalam, and hadith. Islamic rational-philosophical thought was born not from outsiders but from its holy book, namely the Koran, especially in relation to efforts to adapt the teachings of the text to the realities of everyday life. There are at least three models of formal study which turn out to have philosophical relevance. Among other things, (1) the use of takwîl. (2) musytarak and (3) the use of qiyâs (analogy). Al Kindi has introduced new problems in Islamic thought and left behind philosophical problems that persist today: (1) the creation of the universe, how it came about, (2) the immortality of the soul, what it means and how to prove it, and (3) knowledge of God, what does astrology have to do with it and how did it happen. There are two reasons it is called Islamic philosophy.